SOSIALISASI PENGENALAN SOFTWARE GOOGLE FORM SEBAGAI ALAT DIGITAL UNTUK PENGUMPULAN DATA SEKOLAH - Andreas Tan; Asep Setiawan; Itkonul Akbar; Arya Panca; Muhamad Fikri Dzam-Dzam; Hanan Dwiky Masshafy; Adi Tia Setiawan; Naufal Fauzi Akbar; Muhamad Asykal Rizki; Septina Putri Laia; Surtikanti (Abdi Jurnal Publikasi, 2024)
Digital transformation in education has become an essential need to support efficiency in administration and learning processes. One of the solutions that can enhance efficiency in data management is the use of digital tools such as Google Forms. However, many educators and administrative staff have not fully understood how to use this tool. This study aims to improve the understanding and skills of the staff at MTsN 1 Tangerang Selatan in using Google Forms for data collection. The activity was conducted through a socialization session consisting of theory and hands-on practice. Data were collected through observation, interviews, and satisfaction surveys. The results showed that 87% of participants were able to independently create Google Forms after the training, with a satisfaction rate of 90%. However, some participants still faced difficulties with advanced settings, such as data analysis and notification settings. Based on these findings, it is recommended that further training be provided to deepen participants' understanding of Google Forms' advanced features. The use of Google Forms can improve the efficiency of data management in schools, but participants' readiness to adopt new technology still affects the effectiveness of the training.